The role of socioeconomic status in different trajectories of depressive symptoms in Chinese college freshmen - Liu, Qingying; Tan, Junying; Feng, Zhengzhi; Tu, Shen (Frontiers in Psychology, 2022)
The associations between socioeconomic status (SES) and depressive symptoms have been found in previous studies. However, the role of SES in different trajectories of depressive symptoms in Chinese college freshmen has not been discovered. The present study aims to identify how depressive symptom trajectories are related to socioeconomic status during the first semester of freshman. Six hundred fifty-two Chinese college freshmen ( 64.9% female) were followed 4 times across 4 months. The Latent Growth Mixture Model (LGMM) was used to identify trajectories of depressive symptoms. Multinomial Logical Regression was used to identify the influence of family socioeconomic status, subjective socioeconomic status, and demographic variables on trajectories of depressive symptoms for freshmen. Results found that college freshmen’s depressive symptoms gradually decreased during the four tests, F(2.758, 1795.383) = 52.642, p < .001, and there are three trajectories of depressive symptoms: normal group (Class 1, 73.1%), depression risk group (Class 2, 20.7%), and depression deterioration group (Class 3, 6.1 %). The decline of subjective socioeconomic status predicted increasing depressive symptoms. Age and left-behind experience have significant effects on trajectories of depressive symptoms. Family socioeconomic status, birthplace, and gender had no significant impact on trajectories of depressive symptoms. These results demonstrated that low subjective socioeconomic status, age, and left-behind might be risk factors for the development of depressive symptoms.